Inhibition of mycotoxin-producing Aspergillus nomius VSC 23 by lactic acid bacteria and Saccharomyces cerevisiae - Muñoz, R. (2010)
The effect of different fermenting microorganisms on growth of a mycotoxin- producing Aspergillus nomius was assayed. Two lactic acid bacteria, Lactobacillus fermentum and Lactobacillus rhamnosus, and Saccharomyces cerevisiae, all of which are widely used in fermentation and preservation of food, were assayed on their fungus inhibitory properties. Assays were carried out by simultaneous inoculation of one of the possible inhibiting microorganisms and the fungus or subsequent inoculation of one of the microorganisms followed by the fungus. All three microorganisms assayed showed growth inhibition of the mycotoxin-producing Aspergillus strain. L. rhamnosus O236, isolated from sheep milk and selected for its technological properties, showed highest fungal inhibition of the microorganisms assayed. The use of antifungal LAB with excellent technological properties rather than chemical preservatives would enable the food industry to produce organic food without addition of chemical substances.